2021
DOI: 10.1088/1674-1056/abe374
|View full text |Cite
|
Sign up to set email alerts
|

A super-junction SOI-LDMOS with low resistance electron channel

Abstract: A novel super-junction LDMOS with low resistance channel (LRC), named LRC-LDMOS based on the silicon-on-insulator (SOI) technology is proposed. The LRC is highly doped on the surface of the drift region, which can significantly reduce the specific on resistance (R on,sp) in forward conduction. The charge compensation between the LRC, N-pillar, and P-pillar of the super-junction are adjusted to satisfy the charge balance, which can completely deplete the whole drift, thus the breakdown voltage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Numerous investigations have demonstrated that the maximum electric field in LDMOS power devices is predominantly concentrated at the drain side adjacent to the gate edge. This highlights that this particular point is highly susceptible to high drain voltage [38][39][40][41][42][43] . Therefore, to increase the breakdown voltage, it becomes imperative to mitigate the peak electric field and achieve a more uniform surface electric field.…”
Section: Improvement For the Breakdown Voltagementioning
confidence: 90%
“…Numerous investigations have demonstrated that the maximum electric field in LDMOS power devices is predominantly concentrated at the drain side adjacent to the gate edge. This highlights that this particular point is highly susceptible to high drain voltage [38][39][40][41][42][43] . Therefore, to increase the breakdown voltage, it becomes imperative to mitigate the peak electric field and achieve a more uniform surface electric field.…”
Section: Improvement For the Breakdown Voltagementioning
confidence: 90%